Comparative Evaluation of Flexural Strength and Impact Strength of Heat Cure Acrylic Denture Base Reinforced with Nanoparticles of Zirconium Oxide, Peek and Glass Fibers- An In-Vitro Study - Dr. Medhavi Sahu; Dr. Priyabrata Jena; Dr. Saumya Sharma; Dr. Sanjeev Singh; Dr. Arpana Verma; Dr Neeraj Kumar Gupta (The Bioscan, 2025)
Aim: The aim of this study is to compare the Flexural Strength and Impact Strength of PMMA with PMMA reinforced with nanoparticles of Zirconium Oxide, Polyetheretherketone and Silanized E-Glass Fibres. Materials and Methods: A total of one hundred and twenty specimens were fabricated. Out of 120 specimens, sixty specimens were fabricated to evaluate Flexural Strength (dimensions: 65mm x 10mm x 2.5mm) and another sixty specimens to evaluate Impact Strength (dimensions: 80mm x 10mm x 4mm). Flexural strength testing conducted using the three-point bending test in a universal testing machine. Impact Strength Testing conducted using Charpy and Izod testing machine. A one-way analysis of variance (ANOVA) was performed to evaluate statistically significant differences among the groups for both flexural and impact strength. Following this, Tukey’s post hoc test was employed for intra-group comparisons. Results: PMMA reinforced with PEEK nanoparticles (Group P) exhibited the highest mean flexural strength (55.08±12.91), followed closely by PMMA reinforced with Glass Fibers (Group G) (52.62±11.26). The control group (PMMA) had the highest mean impact strength (34.95±10.62), followed closely by the Glass Fibers group (33.96±11.64), and then the PEEK group (31.54±11.31). Conclusion: PEEK and glass fibers are more effective reinforcements for improving the mechanical performance of PMMA, particularly in applications requiring greater flexural strength.